Inhibitory Regulation of Skin Fibrosis in Systemic Sclerosis by Apelin/APJ Signaling. Issue 10 (23rd August 2018) - Yokoyama, Yoko; Sekiguchi, Akiko; Fujiwara, Chisako; Uchiyama, Akihiko; Uehara, Akihito; Ogino, Sachiko; Torii, Ryoko; Ishikawa, Osamu; Motegi, Sei‐ichiro
Abstract : Objective: Apelin/APJ signaling has been determined to regulate cardiac and arterial fibrosis and to be involved in the pathogenesis of pulmonary arterial hypertension. Our objective was to elucidate the role of apelin in skin fibrosis in systemic sclerosis (SSc). Methods: Expression of apelin/APJ in normal and SSc fibroblasts was compared. Effects of small interfering RNA depletion and the addition of apelin in fibroblasts were analyzed. The effect of apelin injections on bleomycin‐induced dermal fibrosis in mice was investigated. We analyzed the effects of the biased agonist of APJ, MM07, on skin fibrosis in vitro and in vivo. Results: The expression of apelin in SSc fibroblasts was significantly lower than that in normal fibroblasts. Serum apelin levels were negatively correlated with the modified Rodnan skin thickness score in SSc patients. Stimulation with transforming growth factor β1 (TGFβ1) inhibited apelin expression in fibroblasts, suggesting that activation of TGFβ1 signaling in SSc might be responsible for reduced apelin expression in SSc fibroblasts. Small interfering RNA depletion of apelin from fibroblasts significantly enhanced fibrosis‐related gene expression, and treatment with apelin protein significantly inhibited TGFβ1 signaling in fibroblasts. Administration of apelin significantly inhibited bleomycin‐induced dermal fibrosis in mice. We demonstrated that MM07 had greater potential than apelin to inhibit fibrosis in vivo and in vitro. Conclusion: Collectively, TGFβ1 signaling and apelin signaling may counteract each other in the fibrotic process of SSc. Inhibitory regulation of TGFβ1‐induced skin fibrosis by apelin/APJ signaling may be involved in the pathogenesis of SSc and could be a therapeutic target for fibrosis in SSc patients.